The Psychoeducational Review of Religion and Culture in Early Childhood through "Terbang Barong" Dance - Ervin Nuriana; Warih Handayaningrum; Setyo Yanuartuti; Arif Hidajat (Jurnal Pelita PAUD, 2026)
Religious and cultural values in early childhood are important provisions and foundations in the period of early childhood character formation. This paper aims to examine the role through a psychoeducational approach in integrating spiritual and cultural values through the medium of children's dance movements, especially children's dance entitled "Flying Barong". This dance combines elements of the art tradition of barongan and jaranan with the accompaniment of Islamic music and the use of tambourine properties as an exploratory medium for children's movements as well as Islamic symbols as a plaything of the dance concept. A descriptive qualitative approach was used to analyze the relevance of dance movements to aspects of child development, especially spiritual, emotional, social, and kinesthetic development. The results of the study show that Dance Flying Barong It is effective as a psychoeducational tool that strengthens children's spiritual awareness through religious habits, such as prayer and empathy, as well as introducing local cultural values in a contextual and fun way. This dance also helps children in the development of emotional regulation, social collaboration, and creative expression. This study recommends the integration of dance with religious-cultural nuances as a learning medium in early childhood education to form a complete character and rooted in local values.